Changes in the higher-level functional capacities for modern daily living in community-dwelling stroke survivors: A preliminary case series - Kawasaki, Tsubasa; Ohira, Masahiro; Endo, Ryu; Muto, Keita; Sakai, Hiroki; Goto, Keisuke (Frontiers in Neurology, 2022)
Along with the development of modern technology, the variety of higher-level activities of daily living has steadily expanded. However, no reports have examined the capacities for the higher-level activities in stroke survivors. Moreover, the relationship between these capacities and executive functions has not been reported. This preliminary study longitudinally measured changes in the capacities for high-level activities of modern daily living in community-dwelling stroke survivors. In addition, we examined whether changes in these capacities were correlated with executive functions. The results showed no significant reduction in the capacities for high-level activities of modern daily living at one year after stroke. Significant improvements were observed in one aspect of executive functions: planning. The changes in the capacities for higher-level activities of modern daily living were significantly correlated with executive function. The results suggest that, in stroke survivors, (a) it is likely feasible to maintain the capacities for higher-level activities of modern daily living, and (b) these capacities are related to executive functions.